Implementation of Building Information Modelling (BIM) in Malaysia: a review - Haron, Nuzul Azam; Raja Soh, Raja Putri Zarifh Ana; Harun, Aizul Nahar (Universiti Putra Malaysia Press, 2017)
This paper seeks to clarify Building Information Modelling (BIM) and its implementation in Malaysia. Most developed countries that have implemented BIM in the construction industry have found it effective. This paper reviews existing literature on the implementation of BIM and examines the implementation strategies that have been developed. The review highlights numerous advantages of BIM in construction, which include, among others, reducing cost, time, carbon burden and capital cost. BIM can also help increase broader efficiencies and improve coordination and communication between each party. However, implementing BIM is complicated and requires efforts from both the government and the private sector. While the implementation of BIM may reduce costs in developed countries, it may not do so in developing countries; in Malaysia, for instance, costs act as an initial barrier. Other obstacles to implementing BIM in Malaysia include application system requirements and lack of knowledge and readiness to change. To facilitate its implementation in the construction industry, the Malaysian government needs to hold seminars to promote a better understanding of BIM. They may also introduce a properly structured BIM course by preparing a standard code of practices and guidelines for BIM in the education sector.